Job Crafting dan Persepsi Dukungan Organisasi terhadap Kinerja Karyawan melalui Keterikatan Kerja - SETIA YULIVIANTO, TRI (Jurnal Ilmu Manajemen (JIM), 2019)
The objective of this study is to test and analyze the effect of job crafting and perceived organizational support on the employee performance through work engagement as an intervening variable in PT. Garam (Persero). This study is a causality study with a quantitative approach. The sampling technique in this study uses proportionate stratified random sampling with a total sample of 98 employees from a total population of 130 permanent employees in all divisions at PT. Garam (Persero). The statistical analysis used in this study is Partial Least Square (PLS) with the help of smartPLS 3.0 software. The results of this study explain that job crafting and work engagement has a positive and significant effect on the employee performance. Job crafting has a positive and significant effect on work engagement. Perceived organizational support does not have an effect on the work engagement and employee performance. Work engagement successfully mediates the relationship between job crafting and employee performance, but does not succeed in mediating the relationship between perceived organizational support and employee performance, Keywords: employee performance; job crafting; perceived of organizational support; work engagement